Long-range angular correlations on the near and away side in p-Pb collisions at √SNN=5.02 TeV - Abelev, Betty; Adam, Jaroslav; Adamova, Dagmar; Adare, Andrew Marshall; Aggarwal, Madan; Rinella, Gianluca Aglieri; Agnello, Michelangelo; Agocs, Andras Gabor; Agostinelli, Andrea; Ahammed, Zubayer; Ahmad, Nazeer; Ahmad, Arshad; et al. (ELSEVIER, 2013)
Angular correlations between charged trigger and associated particles are measured by the ALICE detector in p-Pb collisions at a nucleon-nucleon centre-of-mass energy of 5.02 TeV for transverse momentum ranges within 0.5 < P-T,P-assoc < P-T,P-trig < 4 GeV/c. The correlations are measured over two units of pseudorapidity and full azimuthal angle in different intervals of event multiplicity, and expressed as associated yield per trigger particle. Two long-range ridge-like structures, one on the near side and one on the away side, are observed when the per-trigger yield obtained in low-multiplicity events is subtracted from the one in high-multiplicity events. The excess on the near-side is qualitatively similar to that recently reported by the CMS Collaboration, while the excess on the away-side is reported for the first time. The two-ridge structure projected onto azimuthal angle is quantified with the second and third Fourier coefficients as well as by near-side and away-side yields and widths. The yields on the near side and on the away side are equal within the uncertainties for all studied event multiplicity and p(T) bins, and the widths show no significant evolution with event multiplicity or p(T). These findings suggest that the near-side ridge is accompanied by an essentially identical away-side ridge. (c) 2013 CERN. Published by Elsevier B.V. All rights reserved.
Keywords: PROTON-PROTON COLLISIONS; TRIANGULAR FLOW; Astronomy & Astrophysics; Physics